A high-throughput liquid biopsy for rapid rare cell separation from large-volume samples. Issue 1 (5th December 2018) - Liu, Yaoping; Li, Tingyu; Xu, Mingxin; Zhang, Wei; Xiong, Yan; Nie, Ligong; Wang, Qi; Li, Haichao; Wang, Wei
Abstract : The developed high-throughput liquid biopsy platform for rare tumor cell separation from body fluids has shown enormous promise in cancer detection and prognosis monitoring. Abstract : Liquid biopsy techniques for rare tumor cell separation from body fluids have shown enormous promise in cancer detection and prognosis monitoring. This work established a high-throughput liquid biopsy platform with a high recovery rate and a high cell viability based on a previously reported 2.5D micropore-arrayed filtration membrane. Thanks to its high porosity (>40.2%, edge-to-edge space between the adjacent micropores <4 μm), the achieved filtration throughputs can reach >110 mL min −1 for aqueous samples and >17 mL min −1 for undiluted whole blood, only driven by gravity with no need for any extra pressure loading. The recoveries of rare lung tumor cells (A549s) spiked in PBS (10 mL), unprocessed BALF (10 mL) and whole blood (5 mL) show high recovery rates (88.0 ± 3.7%, 86.0 ± 5.3% and 83.2 ± 6.2%, respectively, n = 5 for every trial) and prove the high performance of this platform. Successful detection of circulating tumor cells (CTCs) from whole blood samples (5 mL) of lung cancer patients ( n = 5) was demonstrated. In addition, it was both numerically and experimentally proved that a small edge-to-edge space was significant to improve the viability of the recovered cells and the purity of the target cell recovery, which was reported for the first time to the best of the authors' knowledge. This high-throughput technique will expand the detecting targets of liquid biopsy from the presently focused CTCs in whole blood to the exfoliated tumor cells (ETCs) in other large-volume clinical samples, such as BALF, urine and pleural fluid. Meanwhile, the technique is easy to operate and ready for integration with other separation and analysis tools to fulfill a powerful system for practical clinical applications of liquid biopsy.